TRANSITION TO GREEN ENERGY IN UZBEKISTAN: ANALYSIS OF FINANCIAL RISKS AND OPPORTUNITIES FOR INDUSTRIAL ENTERPRISES - N. Turaeva (European Science Publishing, 2025)
This article analyzes the financial opportunities and risks for industrial enterprises in Uzbekistan as part of the transition to green energy. Transforming the energy sector of the country economic growth and ecological stability in providing important factor industry in the sector this process separately to the point owner. In the article this in the field state policy, investment environment, technology condition as well as financial obstacles and them elimination verb according to recommendations seeing It is released.
Keywords: Green energy, industry enterprises, financial risk, investment, Uzbekistan, re renewable energy sources, energy efficiency.